2013
DOI: 10.1016/j.ijppaw.2012.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Tick infestation patterns in free ranging African buffalo (Syncercus caffer): Effects of host innate immunity and niche segregation among tick species

Abstract: Graphical abstractHighlights► Rhipicephalus evertsi evertsi and Amblyomma hebraeum are abundant on wild African buffalo. ► The two tick species do not affect each other’s abundance. ► Strong differences in attachment site preference suggest spatial niche segregation. ► Host traits (immunity, age, pregnancy status, body condition) drive tick abundance. ► Buffalo with stronger innate immunity have fewer ticks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 96 publications
3
33
0
Order By: Relevance
“…Poor body condition in animals can be associated with poor management and nutritional status (Radostits, 2001). In particular, malnutrition can result into the lowering and deppression of the immune system and this, in turn, increases suceptibility of the animals to diseases and tick infestation, and failure to respond to vaccines and drugs (Radostits, 2001;Anderson et al, 2013). Our findings concur with other studies reported in Ethiopia (Tadesse et al, 2012;Onu and Sheferaw, 2013;Wogayehu et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Poor body condition in animals can be associated with poor management and nutritional status (Radostits, 2001). In particular, malnutrition can result into the lowering and deppression of the immune system and this, in turn, increases suceptibility of the animals to diseases and tick infestation, and failure to respond to vaccines and drugs (Radostits, 2001;Anderson et al, 2013). Our findings concur with other studies reported in Ethiopia (Tadesse et al, 2012;Onu and Sheferaw, 2013;Wogayehu et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Like other parasites, ticks are found on only a subset of all apparently suitable hosts (Randolph, 2004), and which host characteristics drive ecological patterns in tick parasitism remains poorly resolved. While some studies have found clear relationships between intraspecific host traits and tick burdens (Tälleklint and Jaenson, 1997, Hughes and Randolph, 2001, Harrison et al., 2010, Vor et al., 2010, Kiffner et al., 2011a, Kiffner et al., 2011b, Anderson et al., 2013, Heylen et al., 2013), others have not (Brunner and Ostfeld, 2008, Pollock et al., 2012). These earlier studies, however, largely focused on a single tick species, mostly from the Ixodes ricinus species complex, and its distribution across one or two host species.…”
Section: Introductionmentioning
confidence: 99%
“…Measures of the immune function have seldom been causally related to ectoparasite burdens and rarely for a tick species on a wild host (Anderson et al 2013). However, it is expected that a weakened immune function of hosts affects positively parasite fitness (Krasnov et al 2005;Beldomenico and Begon 2010;Anderson et al 2013). Here, a negative association between I. loricatus NN and WBC became apparent in individuals with moderate to high burdens of A. triste.…”
Section: Discussionmentioning
confidence: 99%
“…The factors evaluated included those known to have the potential to influence ectoparasite burdens (i.e. host sex, age, physiological condition and immune response; season; host abundance) (Hughes and Randolph 2001;Soliman et al 2001;Brunner and Ostfeld 2008;Kiffner et al 2011;Nava et al 2011;Anderson et al 2013), environmental variables that result from dominant human activities in the study area (cattle and implanted forests), and also the often ignored accompanying ectoparasite community.…”
Section: Introductionmentioning
confidence: 99%